New Hart's rules the Oxford style guide. - Waddingham, Anne (Oxford Oxford University Press, 2014)
For over a hundred years, Hart's Rules has been the authority on style, helping writers and editors prepare copy for publication. The latest edition of this guide has been updated for the twenty-first century using the resources of Oxford Dictionaries and with the advice of publishing experts. Twenty-one chapters give information on all aspects of writing and of preparing copy for publication, whether in print or electronically. New Hart's Rules gives guidance on a broad range of topics including publishing terms, layout and headings, how to treat illustrations, hyphenation, punctuation, and bi.
Adapted from the Oxford guide to style, 2002 by R.M. Ritter; first edition published in 2005.
Keywords: Authorship -- Style manuals; Editing -- Handbooks, manuals, etc; English language -- Style -- Handbooks, manuals, etc